Building a Global Food Systems Typology: A New Tool for Reducing Complexity in Food Systems Analysis - Marshall, Quinn; Fanzo, Jessica; Barrett, Christopher B.; Jones, Andrew D.; Herforth, Anna; McLaren, Rebecca (Frontiers in Sustainable Food Systems, 2021)
Food systems have a profound impact on diets, nutrition, health, economic development, and environmental sustainability. Yet their complexity poses a persistent challenge in identifying the policy actions that are needed to improve human and planetary health outcomes. Typologies are a useful classification tool to identify similarities and differences among food systems, while reducing this analytical complexity. This study presents a new food system typology, implemented at the country level using parsimonious data that characterize food supply chains, food environments, consumer-related factors, and key outcomes, including dietary intake, nutritional status, health, and environmental impacts. Five food system types are identified: rural and traditional; informal and expanding; emerging and diversifying; modernizing and formalizing; and industrial and consolidated. Patterns across the five system types in key outcomes variables align with narratives provided by the food systems and nutrition transition literature, demonstrating the usefulness of this classification method. Substantial heterogeneity nonetheless still exists within individual food system types. Therefore, the recommended use of the typology is in early stages of hypothesis generation, to identify potential risk factors or constraints in the food system that can be explored further at national and sub-national levels.